Diagnosis and Management of Trauma to the Trachea and Bronchi - Peters, Katherine; Thunell, Jessica; Karmy-Jones, Riyad (Current Respiratory Medicine Reviews, 2015)
Tracheobronchial injuries are uncommon, occuring in as few as 0.5% of patients following injury. The incidence is highest following penetrating neck and the lowest as 2% following blunt chest injury. While commonly presenting as immediately life threatening injuries, they may present in a more occult fashion with late onset of hemoptysis, recurrent pneumonia and/or “asthma.” Management must be immediately directed to securing the airway, which may require advanced bronchoscopic skills. Subsequent repair must take into account the severity of associated injuries and exact location and degree of airway disruption.
Keywords: trachea